A Low Cost Automated Table Tennis Launcher - Ponnusamy, Barath; Wong, Fei Yong; Zulkifli, Ahmad@Manap (Asian Research Publishing Network (ARPN), 2015)
The purpose of this project is to innovate a low-cost table tennis robot with unique control system. Currently, the available table tennis robots are very expensive, and almost all of them are with wired controller where the player himself cannot control the machine when training sessions. A new design and concept are developed in order to solve these problems. This innovation called automated table tennis launcher, a self-table tennis training kit prototype which is integrated with a microcontroller better known as Arduino. This machine is controlled by the use of Android smart phones to enhance the user-friendliness and the use of wooden support and PVC pipes to fabricate greatly reduces the manufacturing cost. A 3D virtual prototype is developed by using SolidWorks software before the fabrication process and tested for function ability. This fabricated prototype can shoot the ball in three different directions and with adjustable spinning direction, which helps the user to practice almost all types of strokes in this sport. The machine is being tested and analyzed in terms of ball speed, ball shooting coverage, feeding rate and shooting distance. The results show reliable data where this machine could develop a player’s ability to return the ball with proper strokes as well as improve the player’s reaction. Furthermore, this machine is considerably very cheap for its function compared to the currently marketed products. As a conclusion, this automated table tennis launcher able to function as expected and can perform better when fabricated into the real products by using the customized size for every part.